SOME THEORETICAL AND LEGAL ASPECTS OF INTERNATIONAL AND NATIONAL LEGAL REGULATION OF CROSS-BORDER COOPERATION IN UKRAINE - ViktoriiaHolubieva (The journal of contemporary issues in business and government, 2021)
The article is aimed at generalizing modern trends in international and national, as well as institutional and legal regulation/support of international regional cross-border cooperation, overcoming a terminology accretion, which allows various forms of interstate and intrastate cross-border cooperation to be implemented.A number of improvements concerning the concepts of cross-border, inter-territorial, regional and integration cooperation, border, sub-regional/local, partnership/fraternal cooperation, territorial/local partnership/fraternal cooperation are proposed. In addition, the forms of cross-border cooperation are defined. The principal national legal and regulatory acts of Ukraine, which are within legal boundaries related to support/regulation of cross-border cooperation, are examined. As a result,it is stated that there is an international and national legal basis for Ukraine carrying out cross-border and interregional cooperation with border states, namely EU members.